A Double-blind, Randomized, Placebo-controlled Trial of Lactobacillus acidophilus for the Treatment of Acute Watery Diarrhea in Vietnamese Children. Issue 1 (January 2018) - Hong Chau, Tran Thi; Minh Chau, Nguyen Ngoc; Hoang Le, Nhat Thanh; Chung The, Hao; Voong Vinh, Phat; Nguyen To, Nguyen Thi; Ngoc, Nguyen Minh; Tuan, Ha Manh; Chau Ngoc, Tang Le; Kolader, Marion-Eliette; Farrar, Jeremy J.; Wolbers, Marcel; et al.
Abstract : Background: Probiotics are the most frequently prescribed treatment for children hospitalized with diarrhea in Vietnam. We were uncertain of the benefits of probiotics for the treatment of acute watery diarrhea in Vietnamese children. Methods: We conducted a double-blind, placebo-controlled, randomized trial of children hospitalized with acute watery diarrhea in Vietnam. Children meeting the inclusion criteria (acute watery diarrhea) were randomized to receive either 2 daily oral doses of 2 × 10 8 CFUs of a local probiotic containing Lactobacillus acidophilus or placebo for 5 days as an adjunct to standard of care. The primary end point was time from the first dose of study medication to the start of the first 24-hour period without diarrhea. Secondary outcomes included the total duration of diarrhea and hospitalization, daily stool frequency, treatment failure, daily fecal concentrations of rotavirus and norovirus, and Lactobacillus colonization. Results: One hundred and fifty children were randomized into each study group. The median time from the first dose of study medication to the start of the first 24-hour diarrhea-free period was 43 hours (interquartile range, 15–66 hours) in the placebo group and 35 hours (interquartile range, 20–68 hours) in the probiotic group (acceleration factor 1.09 [95% confidence interval, 0.78–1.51]; P = 0.62). There was also no evidence that probiotic treatment was efficacious in any of the predefined subgroups nor significantly associated with any secondary end point. Conclusions: This was a large double-blind, placebo-controlled trial in which the probiotic underwent longitudinal quality control. We found under these conditions that L. acidophilus was not beneficial in treating children with acute watery diarrhea. Abstract : Supplemental Digital Content is available in the text.